Fabrication of Nanoformulation Containing Carvedilol and Silk Protein Sericin against Doxorubicin Induced Cardiac Damage in Rats - Mohammad Shariq; Tarique Mahmood; Poonam Kushwaha; Saba Parveen; Arshiya Shamim; Farogh Ahsan; Tanveer A. Wani; Seema Zargar; Rufaida Wasim; Muhammad Wahajuddin (MDPI AG, 2023)
Nanotechnology has emerged as an inspiring tool for the effective delivery of drugs to help treat Coronary heart disease (CHD) which represents the most prevalent reason for mortality and morbidity globally. The current study focuses on the assessment of the cardioprotective prospective ofanovel combination nanoformulation of sericin and carvedilol. Sericin is a silk protein obtained from Bombyx mori cocoon and carvedilol is a synthetic nonselective β-blocker. In this present study, preparation of chitosan nanoparticles was performed via ionic gelation method and were evaluated for cardioprotective activity in doxorubicin (Dox)-induced cardiotoxicity. Serum biochemical markers of myocardial damage play a substantial role in the analysis of cardiovascular ailments and their increased levels have been observed to be significantly decreased in treatment groups. Treatment groups showed a decline in the positivity frequency of the Troponin T test as well. The NTG (Nanoparticle Treated Group), CSG (Carvedilol Standard Group), and SSG (Sericin Standard Group) were revealed to have reduced lipid peroxide levels (Plasma and heart tissue) highly significantly at a level of p < 0.01 in comparison with the TCG (Toxic Control Group). Levels of antioxidants in the plasma and the cardiac tissue were also established to be within range of the treated groups in comparison to TCG. Mitochondrial enzymes in cardiac tissue were found to be elevated in treated groups. Lysosomal hydrolases accomplish a significant role in counteracting the inflammatory pathogenesis followed by disease infliction, as perceived in the TCG group. These enzyme levels in the cardiac tissue were significantly improved after treatment with the nanoformulation. Total collagen content in the cardiac tissue of the NTG, SSG, and CSG groups was established to be highly statistically significant at p < 0.001 as well as statistically significant at p < 0.01, respectively. Hence, the outcomes of this study suggest that the developed nanoparticle formulation is effective against doxorubicin-induced cardiotoxicity.